Is avolition in schizophrenia associated with a deficit of dorsal caudate activity? A functional magnetic resonance imaging study during reward anticipation and feedback. Issue 8 (12th January 2015) - Mucci, A.; Dima, D.; Soricelli, A.; Volpe, U.; Bucci, P.; Frangou, S.; Prinster, A.; Salvatore, M.; Galderisi, S.; Maj, M.
Abstract : Background: The neurobiological underpinnings of avolition in schizophrenia remain unclear. Most brain imaging research has focused on reward prediction deficit and on ventral striatum dysfunction, but findings are not consistent. In the light of accumulating evidence that both ventral striatum and dorsal caudate play a key role in motivation, we investigated ventral striatum and dorsal caudate activation during processing of reward or loss in patients with schizophrenia. Method: We used functional magnetic resonance imaging to study brain activation during a Monetary Incentive Delay task in patients with schizophrenia, treated with second-generation antipsychotics only, and in healthy controls (HC). We also assessed the relationships of ventral striatum and dorsal caudate activation with measures of hedonic experience and motivation. Results: The whole patient group had lower motivation but comparable hedonic experience and striatal activation than HC. Patients with high avolition scores showed lower dorsal caudate activation than both HC and patients with low avolition scores. A lower dorsal caudate activation was also observed in patients with deficit schizophrenia compared to HC and patients with non-deficit schizophrenia. Dorsal caudate activity during reward anticipation was significantly associated with avolition, but not with anhedonia in the patient group. Conclusions: These findings suggest that avolition in schizophrenia is linked to dorsal caudate hypoactivation.